RATIONAL DRUG USE (RDU) BASED ON PATIENT CARE INDICATOR IN PRIMARY HEALTH CENTER IN SEMARANG - Nisa Febrinasari; Arifin Santoso; Abdur Rosyid; Aditya Dwi Meilani (Jurnal Farmasi Sains dan Praktis, 2021)
Rational Drug Use has several indicators, one of which is service indicators, where service indicators will play a role in increasing rational drug use so that it can support the success of treatment to achieve a better quality of life and patient welfare. The purpose of this study was to determine rational drug use in the city of Semarang based on service indicator parameters. This research is a descriptive-analytic with a cross-sectional design, data collection is done prospectively with a direct observation approach and direct interviews with respondents. The number of respondents was 744 patients (372 at Puskesmas N and 372 at Puskesmas TK who were taken by consecutive sampling. The data were processed using the Mann-Whitney statistical test with a p-value <0.05. The results of this study indicate that the use of drugs in Puskesmas N and Puskesmas TK There is a significant difference with a p-value <0.05. In the meantime of medical consultation 5-11 minutes; the average time for drug preparation 10-16 minutes; the percentage of drug delivery suitability is 100%; the percentage of adequate labeling is 100% and the percentage of knowledge Patients at the puskesmas approach rationality and there are differences in services between the two Puskesmas. The government needs to increase the number of pharmacists and improve infrastructure, especially in terms of drug counseling at each puskesmas so that it is hoped that patient knowledge of the drug regimen to be consumed will increase.